2016
DOI: 10.1177/0885328216672947
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the unexpected influence of the Si:Ge ratio on the molecular architecture and mechanical properties of Al-free GICs

Abstract: Germanium (Ge)-based glass ionomer cements have demonstrated the ability to balance strength with extended setting times, a unique set of characteristics for aluminum-free glass ionomer cements. However, the mechanical properties of current Ge-based glass ionomer cements significantly deteriorate over time, which jeopardizes their clinical potential. This work explores the effect of incrementally decreasing the Si:Ge ratio in the glass phase of zinc-silicate glass ionomer cements to identify potential mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…A possible explanation for this toxicity reduction is a chemical interaction that occurs between HAp and CaF 2 , triggering an ion exchange and consequently the removal of fluoride from the local environment. This phenomenon confirms that GICs have the ability to bind chemically with tooth structures after a setting reaction (23-25).…”
Section: Discussionsupporting
confidence: 72%
“…A possible explanation for this toxicity reduction is a chemical interaction that occurs between HAp and CaF 2 , triggering an ion exchange and consequently the removal of fluoride from the local environment. This phenomenon confirms that GICs have the ability to bind chemically with tooth structures after a setting reaction (23-25).…”
Section: Discussionsupporting
confidence: 72%
“…The other constituents were polymeric materials which do not present peaks in an XRD pattern but appear as wide bands due to their amorphous structure. Other studies also showed that SiO 2 is the major component of this material [36][37][38][39][40]. On the other hand, ZrO 2 presented a crystalline structure, with characteristic peaks in the XRD pattern (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Recent investigation regarding the incorporation of germanium (Ge) at the expense of Si has shown great promise for clinical applications. By formulating GPCs using a glass composition of (mole fraction): SiO2 -0.24, GeO2 -0. offering excellent clinical handling properties while maintaining mechanical strengths similar to Ge-free cements (> 50 MPa) [116]. In addition, the incorporation of Ge has been suggested to reduce the release of Zn to negligible levels (< 10 ppm) [116].…”
Section: Promise Of Gpcs For Orthopedic Applicationsmentioning
confidence: 99%